PENERAPAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY ( UTAUT) DALAM MENGANALISIS PENGGUNAAAN MEDIA PEMBELAJARAN BERBASIS SIMULASI - Megawaty, Megawaty; Andriyani, Ria (JURNAL ILMIAH MATRIK, 2015)
Abstract: The use of computer-based learning media network simulation is one of the alternatives in the learning process, Where in the teaching-learning process using a simulator applications such as: virtual box, packet tracer. This research was conducted at SMK city of Palembang who adopted the use of simulation-based learning media class X for class XI. This study aims to determine the extent of the effect of the application of computer-based learning media network simulation of the learning outcomes of students majoring TKJ (Computer Engineering and Networks) at SMK Palembang, determine the level of students abilities in understanding subjects of computer networks, facilitate students in designing a computer network real. The research model used is UTAUT. The results showed that the Performance Expextancy of behavioral intention in the use of instructional media had no significant effect whereas Effort Expextancy and Social Influence on Behavior intention in the use of instructional media significantly. Keywords: Packet Tracer, UTAUT, Simulation